Effect of dust particles on electron energydistribution in glow and afterglow plasmas - Denysenko, I.B.; Azarenkov, N.A.; Ivko, S.; Burmaka, G.; Glazkov, A. (Вопросы атомной науки и техники, 2016)
Analytical expressions describing electron energy probability functions (EEPFs) in glow and afterglow dusty plasmas are obtained from the homogeneous Boltzmann equation for electrons. At large energies in a glow dusty plasma, the quasiclassical approach for calculation of the EEPF is applied. Considering the afterglow case, the analytical expressions are obtained assuming that the electron energy loss is mainly due to momentum-transfer electronneutral collisions and due to deposition of electrons on dust particles. Effect of dust particles on the EEPF is analyzed. Из однородного уравнения Больцмана получены аналитические выражения для функции распределения электронов по энергии (ФРЭЭ) в пылевой плазме в режимах свечения и послесвечения. Для расчёта ФРЭЭ в режиме свечения при больших электронных энергиях применён квазиклассический подход. Для плазмы в режиме послесвечения аналитические выражения получены в предположении, что потери энергии электронов происходят в основном за счёт упругих электрон-нейтральных столкновений и благодаря осаждению электронов на пылевые частицы. Проанализировано влияние пылевых частиц на ФРЭЭ. З однорідного рівняння Больцмана отримано аналітичні вирази для функції розподілу електронів за енергією (ФРЕЕ) в запорошеної плазмi в режимах світіння та післясвітіння. Для розрахунку ФРЕЕ в режимі світіння при великих електронних енергіях застосовано квазікласичний підхід. Для плазми в режимі післясвітіння аналітичні вирази отримані в припущенні, що втрати енергії електронів відбуваються в основному за рахунок пружних електрон-нейтральних зіткнень та завдяки осадженню електронів на пилові частинки. Проаналізовано вплив пилових частинок на ФРЕЕ.